Strategi Program Pengembangan Lingkungan Pelabuhan Sehat di Pelabuhan Sungai Duku Kota Pekanbaru Provinsi Riau - Marna Dewi; Kiswanto Kiswanto; Ahmad Hanafi; Jasrida Yunita; Iswadi Iswadi (Jurnal Kesehatan Komunitas, 2020)
The implementation of Healthy Ports and Healthy Airports is one of the programs carried out by the Class II Pekanbaru Port Health Office with the aim of creating a clean, comfortable and healthy Port area. The problems that occur at Sungai Duku port are human resources, regulations, budgets, SOP, facilities and environmental conditions (water, air, food soil, vectors and animals that transmit disease), The purpose of this research is to formulate a strategy for a healthy port development program in Sungai Duku port, Pekanbaru City, Riau Province Th 2020, organizational weaknesses and internal organizational opportunities and organizational threats, planning alternative strategies and selecting strategies to achieve the goal of a healthy port. This study used a qualitative method with a descriptive design with a survey method. This research was conducted in April 2020 at Sungai Duku Port, Pekanbaru City, Riau Province and the surrounding environment, the respondents of this study involved 6 people. The variables of this research are human resources, regulations, budget, SOP, facilities and environmental conditions (water, air, food soil, vectors and disease-transmitting animals). The research results were obtained with the SO strategy by utilizing the port environmental conditions that are still good, support from the government and the community and increasing supervision and socialization. The conclusions were power identification and internal organization weakness, looking for alternative strategy such SO, WO, ST, WT, and alternative election. It is recommended that the port manager, the coordinator of Sungai Duku port management (KKP Class II Pekanbaru) and port authorities and related agencies at the port can formulate a healthy port development program based on the SO strategy.